2014
DOI: 10.1515/hsz-2014-0114
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical characterization of polyomavirus minor capsid proteins

Abstract: The murine polyomavirus encodes three structural proteins, VP1, VP2 and VP3, which together form the viral capsid. The outer shell of this capsid is composed of the major capsid protein VP1, the inner shell consists of VP2 and its N-terminally truncated form VP3. These two minor capsid proteins interact with their identical C-terminal part in the central cavity of VP1 pentamers, building the capsid assembly unit. While the VP1 structure and functions are well studied, VP2 and VP3 are poorly understood. In orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The hydrophobic helix was shown to be responsible for interactions of VP2 and VP3 with VP1 pentamers . In addition, computer analysis and circular dichroism spectroscopy of MPyV VP2 and VP3 have revealed that both proteins are highly hydrophobic with a high α‐helical content . In agreement, the viroporins described so far are proteins that contain one or several α‐helices that work as transmembrane domains .…”
Section: Introductionmentioning
confidence: 72%
“…The hydrophobic helix was shown to be responsible for interactions of VP2 and VP3 with VP1 pentamers . In addition, computer analysis and circular dichroism spectroscopy of MPyV VP2 and VP3 have revealed that both proteins are highly hydrophobic with a high α‐helical content . In agreement, the viroporins described so far are proteins that contain one or several α‐helices that work as transmembrane domains .…”
Section: Introductionmentioning
confidence: 72%
“…It might be debated whether JCPyV VP2 can be recognized by the immune system as it was proposed that VP2 is located at the inner side of the capsid [ 42 ]. Crystal structure analysis however showed that the N-terminal part of VP2, including the JCPyV_VP2_167-15mer region is not tightly folded and retains high flexibility, making it easier for VP2 to emerge from inside the virion [ 43 , 44 ]. The fact that it was also shown that 52.3% of serum samples show immunoreactivity with WU Polyomavirus VP2 and 21.9% of blood donors react with SV40 VP2 derived peptides, strengthens the conclusion that JCPyV VP2 acts as an antigen recognized by the immune system upon JCPyV infection [ 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…The participation of agno-protein in viral evolution has been demonstrate in species which express these proteins, including, SV40, JCPyV and BKPyV (Saribas et al, 2016). Study conducted in the previous two decades have exhibits that the expression of VP1 in differ systems promote to the production of structures known as virus -like particles(VLPs), which are same as the viral capsid (Burkert et al, 2014;Touze et al, 2010). After it has expressed, the structural proteins assembled in the cellular nucleus, contributing to the observing of the virion.…”
Section: Biology Polyomavirusmentioning
confidence: 99%